Rising centers in the Inawen low: Its emergence and role in the territorial organisation, Oud Amlil as a model - Neddama, Ali; El-Bazoui, Jaouad; El-Ouardi, Samir; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2024)
The Moroccan geographical sphere is experiencing profound transformations that have made attention to preparing the territory and organizing the national sphere a major priority through the enactment of various policies in order to reduce disparities and reduce the differences resulting from these transformations. Among the areas that can play a vital role in this we find the emerging centers, which play at the local level The role of large and medium cities at the national and regional levels. Therefore, its development is the ideal framework for focusing public efforts with the aim of making it a strong lever for achieving economic and social development at the local level and taking it as a locomotive to accelerate the development of rural areas.The Inawen Basin includes a number of emerging centres, the degree of development of which varies from one center to another. They have benefited from special public policies and have come to provide a range of facilities and services that work to improve the living conditions of the local population by meeting the needs at the level of housing, social services, health, entertainment and education. It was necessary Develop an approach to developing these centers in order to contribute to reducing the social and spatial imbalances and disparities in the Inawen Basin, and to reduce the burden of rural migration borne by neighboring cities such as Fez and Taza. For all these considerations, we decided to address the issue of the emergence of rising centers in the Enawon low and their role in organizing the field through the model of the Umlil Valley Center. We also addressed the topic according to each stage and period, and deduced the forms and manifestations of these transformations. Which forced us to systematically divide the work into two main points as follows: - The historical stages of the growth of the center of the Imlil Valley and its place in the territorial organization of the Enawon low.
Keywords: Centers; emerging; field; transformations; development; territorial; urban